Psychobiologic responses to 4 days of increased training and recovery in cyclists - Filaire, E.; Legrand, B.; Bret, K.; Sagnol, M.; Cottet-Emard, J. M.; Pequignot, J. M. (International Journal of Sports Medicine, 2002)
The psychobiologic status of cyclists after 4 days of training and the kinetics of recovery were assessed by measuring the sympatho-adrenal level, the central noradrenergic activity and the cortisol/testosterone status by non-invasive methods. For this purpose, urinary excretion of methoxyamines (metanephrine [MN], normetanephrine [NMN]), which are metabolites of circulating catecholamines, 3-methoxy-4-hydroxyphenyl glycol sulfate (MHPG-S), a metabolite of brain norepinephrine, and salivary output of cortisol and testosterone were measured in twelve national cyclists (aged 19.5 +/- 4.5 years), just before (T 1 ) and at the end of the training (T 2 ), and during the three following recovery days (R 1, R 2, R 3 ). Urinary and salivary samples were also collected during a period of relative rest, in order to get reference values (T 0 ). At T 0, T 1 and T 2, mood states, as measured by the Profile of Mood States, and rating of perceived muscle soreness were assessed. The overall mood and muscle soreness levels were not affected by the training. The load increased by 187 % as an average between the first and the fourth day of training. A significant increase in NMN levels and a decrease in T:F ratio were observed at T 2, while MHPG-S excretion remained unchanged. Persistent high urinary output of NMN and MN were observed during the post-training recovery period for 24 h (R 1 ) and 48 h (R 2 ), respectively. After 72 h of recovery (R 3 ), MN levels had returned to baseline while NMN output was lower than the control level. T:F values returned to their control levels within 48 h of recovery. The strenuous training seems to induce an alteration in peripheral neuro-endocrine parameters without modifications of central factors. The hormonal status remained altered for at least 1 day of post-training recovery and seemed to be achieved within 3 days.